2015
DOI: 10.3136/fstr.21.537
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Structure of Bread Supplemented with Purple Sweet Potato Powder and Treated with Enzymes

Abstract: Sweet potato a nutritious and abundantly available food crop in many developing countries has been explored for baking to increase its use in food processing. Though it often results in lower quality bread it can be improved with enzyme treatments. Thus, this study evaluated the effect of purple sweet potato powder (PSPP) supplementation, and α-amylase (AM) and hemicellulase (HC) treatments on the texture and retrogradation during storage, and structure of bread. Results showed that PSPP supplementation gave r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Similar studies showed that fiber blends formulations and an increase of the water addition induced a reduction in the specific volume . In addition, results with lower specific volume were related to the reduced number of pores (common in high fiber products) and a higher interaction between the gelatinized starch and gluten network, which was also related with a less capacity of dough gas retention (Santiago et al, 2015). Other studies have also showed that the addition of products with more fiber, for example sweet potato flour or Andean blueberry pulp resulted in a reduction of specific volume (Guijarro-Fuertes et al, 2019;Franco et al, 2020).…”
Section: Bread Characteristicsmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar studies showed that fiber blends formulations and an increase of the water addition induced a reduction in the specific volume . In addition, results with lower specific volume were related to the reduced number of pores (common in high fiber products) and a higher interaction between the gelatinized starch and gluten network, which was also related with a less capacity of dough gas retention (Santiago et al, 2015). Other studies have also showed that the addition of products with more fiber, for example sweet potato flour or Andean blueberry pulp resulted in a reduction of specific volume (Guijarro-Fuertes et al, 2019;Franco et al, 2020).…”
Section: Bread Characteristicsmentioning
confidence: 94%
“…All the parameters were analyzed as response variables in the process mixture design, although not all of them showed significant models. Table 3 shows the mathematical models of the Mixolab parameters, as well as the the rupture force of the bread (Santiago et al, 2015). In general terms, most of the effects were caused due to the partial absence of gluten protein and high fiber content, which also results in a lower gas retention of dough (Santiago et al, 2015).…”
Section: Rheological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bread made of composite flours consider as blends wheat after mixture of two or more flours to produce snack foods, leavened breads, unleavened baked, semibaked and porridges products. Blended or composite flours has become popular because of two main reason namely nutritional and economic benefits ( McWatter et al 2004 ; Santiago et al 2015 ). It might be beneficial to use conposite flour if available local crops resources is utilized that will improve economic condition and accordingly to cut imports pf wheat products ( Khalil et al 2000 ; Murayama et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the damaged starch (DS) and fiber in flour influence gluten formation, resulting in decreased bread making quality (Dexter et al, 1994;Santiago et al, 2015a;Santiago et al, 2015b;Yamauchi et al, 2004a;Yamauchi et al, 2004b). There are various kinds of enzymes used in baking as b r e a d m a k i n g i m p r o v e r s .…”
Section: Introductionmentioning
confidence: 99%